2002
DOI: 10.1530/eje.0.1470117
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase activity in hyperthyroid and hypothyroid rats

Abstract: Objective: Thyroid disorders are accompanied by important changes in haemodynamic and cardiac functions and renal sodium handling. Since nitric oxide (NO) plays a crucial role in regulating vascular tone and renal sodium excretion, the present paper was designed to determine whether changes in the activity of NO synthase (NOS) participate in the cardiovascular and renal manifestations of thyroid disorders. Methods: We measured NOS activity in the heart (left and right ventricles), vessels (aorta and cava) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
56
4
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 34 publications
14
56
4
1
Order By: Relevance
“…Our findings for aortic NOS activity in different thyroid states resemble those reported by Quesada et al (2002). Further, these findings are consistent with earlier findings concerning vascular function.…”
Section: Capacity For No Formationsupporting
confidence: 93%
“…Our findings for aortic NOS activity in different thyroid states resemble those reported by Quesada et al (2002). Further, these findings are consistent with earlier findings concerning vascular function.…”
Section: Capacity For No Formationsupporting
confidence: 93%
“…Various mechanisms or sets of mechanisms might participate in the increased sensitivity to partial NOS blockade in hyperthyroid rats. This study and several reports [13][14][15] provide evidence that the hyperdynamic circulation of hyperthyroidism is accompanied by increased NO production. Anemia 25 and cirrhosis of the liver 26 are also associated with hyperdynamic circulation and increased NO production, and cirrhotic rats also show an increased pressor responsiveness to NO blockade.…”
Section: Discussionsupporting
confidence: 82%
“…13 Fernández et al 14 demonstrated that hyperthyroidism leads to a significant and reversible enhancement in rat liver NOS activity. More recently, our group reported 15 that NOS activity is upregulated in tissues primarily related to BP control in hyperthyroid rats. Our finding suggested that increased NO production might contribute to the hyperdynamic circulation in hyperthyroidism and might have a protective homeostatic effect on the increased BP that accompanies this endocrine disease.…”
mentioning
confidence: 94%
“…These results are similar to findings of previous studies in SHHF rats (5). The exact mechanism of the increase in hypertension in this model is not known and could be caused by any individual factor or combination of factors, including increased body weight, leptin resistance, increased salt sensitivity, increased levels of Ang II, or reduced levels of bradykinin and NO (3,16,24,27,36,37,39).…”
Section: Discussionsupporting
confidence: 91%